2020
DOI: 10.3390/biomedicines8090297
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Effects of Small Molecule Inhibitors and Metal Chelators on Coagulopathic Viperinae Snake Venom Toxins

Abstract: Animal-derived antivenoms are the only specific therapies currently available for the treatment of snake envenoming, but these products have a number of limitations associated with their efficacy, safety and affordability for use in tropical snakebite victims. Small molecule drugs and drug candidates are regarded as promising alternatives for filling the critical therapeutic gap between snake envenoming and effective treatment. In this study, by using an advanced analytical technique that combines chromatograp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 66 publications
2
53
1
Order By: Relevance
“…The comparative testing of the enzyme inhibitors prinomastat and DMPS revealed highly contrasting differences in their specific abilities to neutralize the P-IIId SVMP responsible for FX activation by the venoms in this study. This is congruent with recent data published for FX activation of neonate Crotalus culminatus venom, which prinomastat neutralised but DMPS at the same concentration did not (59) and another report of DMPS requiring long incubation times to exert a discernable effect (60).…”
Section: Discussionsupporting
confidence: 92%
“…The comparative testing of the enzyme inhibitors prinomastat and DMPS revealed highly contrasting differences in their specific abilities to neutralize the P-IIId SVMP responsible for FX activation by the venoms in this study. This is congruent with recent data published for FX activation of neonate Crotalus culminatus venom, which prinomastat neutralised but DMPS at the same concentration did not (59) and another report of DMPS requiring long incubation times to exert a discernable effect (60).…”
Section: Discussionsupporting
confidence: 92%
“…Some of these inhibitors were less effective as therapeutic regimen where the time lapse between venom and administration of inhibitors is prolonged [72]. Moreover, many small molecules and chelators were focused on interference in Viperinae snake venom-induced coagulopathy and local toxicities [69]. However, our findings highlight the efficacy of TTD in ECV-induced both local and systemic toxicities and, would be better repurposing to complement snakebite management.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 78%
“…Besides, TTD has been shown to inhibit MMP-2 and MMP-9 activity by directly interacting with them via a Zn ++ chelating mechanism [66]. Several scientific reports suggested that, many small inhibitors or chelators of SVMPs such as batimastat, marimastat, N,N,N 0 ,N 0 -tetrakis (2-pyridylmethyl) ethane-1,2-diamine and dimercaprol which targets the different classes of SVMPs-induced toxicities [67][68][69][70][71]. Some of these inhibitors were less effective as therapeutic regimen where the time lapse between venom and administration of inhibitors is prolonged [72].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Two contributions from Jeroen Kool’s group examine the usefulness of the small-molecule PLA2 inhibitor Varespladib as a potential drug for the treatment of snake bites. In these studies, cutting-edge nanofractionation analytics are employed to determine the effects of Varespladib and other small molecules on the coagulopathic effects of various crotalid and viperid snake venoms [ 61 , 62 ]. The Hodgson lab examined the neutralising abilities of different antivenoms against the effects of venom from the Chinese cobra by using the chick biventer nerve muscle preparation [ 63 ].…”
Section: Contributions To This Special Issuementioning
confidence: 99%